A population-based case–control study on social factors and risk of testicular germ cell tumours. Issue 9 (20th September 2013) - Schmeisser, Nils; Conway, David I; Stang, Andreas; Jahn, Ingeborg; Stegmaier, Christa; Baumgardt-Elms, Cornelia; Jöckel, Karl-Heinz; Behrens, Thomas; Ahrens, Wolfgang
Abstract : Objectives: Incidence rates for testicular cancer have risen over the last few decades. Findings of an association between the risk of testicular cancer and social factors are controversial. The association of testicular cancer and different indicators of social factors were examined in this study. Design: Case–control study. Setting: Population-based multicentre study in four German regions (city states Bremen and Hamburg, the Saarland region and the city of Essen). Participants: The study included 797 control participants and 266 participants newly diagnosed with testicular cancer of which 167 cases were classified as seminoma and 99 as non-seminoma. The age of study participants ranged from 15 to 69 years. Methods: Social position was classified by educational attainment level, posteducational training, occupational sectors according to Erikson-Goldthorpe-Portocarrero (EGP) and the socioeconomic status (SES) on the basis of the International SocioEconomic Index of occupational status (ISEI). ORs and corresponding 95% CIs (95% CIs) were calculated for the whole study sample and for seminoma and non-seminoma separately. Results: Testicular cancer risk was modestly increased among participants with an apprenticeship (OR=1.7 (95% CI 1.0 to 2.8)) or a university degree (OR=1.6 (95% CI 0.9 to 2.8)) relative to those whose education was limited to school. Analysis of occupational sectors revealed an excess risk for farmers and farm-related occupations. No clear trend was observed for the analyses according to the ISEI-scale. Conclusions: Social factors based on occupational measures were not a risk factor for testicular cancer in this study. The elevated risk in farmers and farm-related occupations warrants further research including analysis of occupational exposures.